Benefits of Impella and Peripheral Veno-Arterial Extra Corporeal Life Support Alliance. Issue 8 (November 2019) - Colombier, Sébastien; Quessard, Astrid; Mastroianni, Ciro; Schmidt, Matthieu; Amour, Julien; Leprince, Pascal; Lebreton, Guillaume
Abstract : Peripheral veno-arterial extra corporeal life support (V-A ECLS) is an effective tool in treating refractory cardiogenic shock (RCS). Despite additional use of intra-aortic balloon pump, insufficient left ventricular unloading is a likely complication. We present herein our experience combining V-A ECLS and Impella to treat symptomatic, critical patients. A retrospective single-center review analyzed patients with V-A ECLS and intra-aortic balloon pump for RCS and subsequently benefiting from Impella implantation, between 2011 and 2015. From 1248 cases, 31 critical patients (2.5%) with a median SOFA score = 12 (7–15) were included. Median age was 53 years, and 74% were male. RCS resulted from myocardial ischemia (52%) and idiopathic dilated myocardiopathy (23%). Forty-seven percentage of patients were treated previously for chronic Heart Failure with reduced Ejection Fraction (HFrEF). Median time between V-A ECLS and Impella implantation was 84 hours (24–186). The Impella median support duration was 8 days (5–10). ECLS and Impella were weaned simultaneously in 26% of patients, 33% were switched to a long-term assistance, and 10% were transplanted. Overall, day-30 survival was 53%. Factors including diabetes, patients aged over 60 years, surgery using extracorporeal circulation, adrenalin infusion, acute myocardial infarction, and chronic HFrEF are associated with day-30 mortality. Chronic HFrEF was an independent risk factor for the day-30 mortality [hazard ratio = 5.28 (1.38–20.21), P = 0.015]. Impella and V-A ECLS combination is a promising association for critical patients presenting symptomatic insufficient LV unloading, for weaning V-A ECLS or testing the right ventricle before a switch to left ventricle assist device support. Abstract : Supplemental Digital Content is available in the text.